Academic tahfiz schools in Malaysia: challenges, insights, and the road forward - Othman, Azam; Nordin, Mohamad Sahari; Nik Abdullah, Nik Md. Saiful Azizi; Ruslan, Norbaiduri (IKSAD GLOBAL Publications, 2022)
Background and aim: Academic Tahfiz Schools offer an alternative system for tahfiz education. In comparison to traditional or pure tahfiz schools, students of academic tahfiz schools memorise the Quran during their schooling years while learning mainstream selected academic subjects within the national curriculum. The main objective of this tahfiz education system is to develop Quran memorisers with good academic qualifications as well as a firm Islamic background who would go into the professional field and similar professions. In Malaysia, there are a small but growing number of government and private Academic Tahfiz Schools. This paper highlights the challenges faced by these types of schools and the potential that they can offer to Muslim communities. Material and Methods: Semi-structured interviews were conducted with five parents, four alumni, and five teachers were conducted and analysed using a two-stage coding process. Results: The themes suggest a set of initial and ongoing challenges that administrators and practitioners need to understand and overcome, especially concerning their current societal needs and environment. Conclusion: This paper concludes with recommendations on how to develop and strengthen this type of institution and its potential for the Muslim ummah.